DETERMINANTS OF PRODUCTIVITY OF RESTAURANT AND DINING MSMEs IN SOUTH KUTA DISTRICT, BADUNG REGENCY - Ni Wayan Nia Lestari Sukantiasih; Putu Ayu Pramitha Purwanti (CV. Adiba Aisha Amira, 2025)
South Kuta District is a strategic area with significant potential for the development of MSMEs, particularly in the culinary sector such as restaurants and eateries that support local tourism. However, the productivity of MSMEs in this area still faces several challenges, including limited access to capital, low utilization of information technology, lack of financial literacy, and suboptimal financial inclusion. This study aims to analyze the influence of business capital, information technology, financial literacy, and financial inclusion on the productivity of restaurant and eatery MSMEs in South Kuta District, Badung Regency, both simultaneously and partially. This research adopts a quantitative approach using the stratified random sampling method based on village and sub-district areas, with a total sample of 100 respondents. The data analysis technique employed is multiple linear regression. The results showthat simultaneously, the four independent variables have a significant influence on MSME productivity. Partially, each variable also demonstrates a positive and significant effect on productivity. These findings indicate that improving access to capital, mastery of technology, financial management literacy, and the expansion of financial services are crucial to enhance the productivity and competitiveness of MSMEs in the tourism sector. Collaboration among government agencies, financial institutions, and business actors is essential to achieve sustainable and inclusive MSME growth.